Complex conductivity in strongly fluctuating layered superconductors - Tinh, B.D.; Thu, L.M.; Hoa, L.V. (Condensed Matter Physics, 2014)
The time-dependent Ginzburg-Landau approach is used to calculate the complex fluctuation conductivity in layered type-II superconductor under magnetic field. Layered structure of the superconductor is accounted for by means of the Lawrence-Doniach model, while the nonlinear interaction term in dynamics is treated within self-consistent Gaussian approximation. In high-Tc materials large portion of the H-T diagram belongs to vortex liquid phase. The expressions summing contributions of all the Landau levels are presented in explicit form which are applicable essentially to whole this phase and are compared to experimental data on high-Tc superconductor YBa₂Cu₃O₇₋δ. Above the crossover to the "normal phase" our results agree with previously obtained. Часозалежним методом Гiнзбурга-Ландау розраховано комплексну флуктуацiйну провiднiсть у шаруватому надпровiднику II-го типу пiд дiєю магнiтного поля. Шарувата структура надпровiдника враховується за допомогою моделi Лоуренса-Доняха, тодi як член, що описує нелiнiйну взаємодiю в динамiцi, розглядається у самоузгодженому гаусовому наближеннi. У високотемпературних матерiалах значна частина дiаграми H ¡T належить до вихорової рiдинної фази. Вирази для сумарного внеску вiд усiх рiвнiв Ландау записанi в явнiй формi. Вони застосовнi по сутi до всiєї цiєї фази i порiвнюються з експериментальними даними для високотемпературного надпровiдника YBa₂Cu₃O₇₋δ. Вище кросовера до “нормальної фази” нашi результати узгоджуються з ранiше отриманими.